Analysis of the UK Information Assurance Industry in relation to the introduction of New Product by Nexor Limited - Sharma, Vibhu (2011)
Nexor Limited identified a gap in the market concerning the tracking of sensitive information within the organisations and hence to address the issue, the research of project codename CARMEN was initiated in 2010 with an aim to capitalise on the growth in the Information Assurance arena. Now, the product is almost ready for the market and hence this project report tries to explore the potential road map for CARMEN in order to reach the target market. The report presents an analysis of the issues involving the loss of the critical information in various industry verticals within UK which include government sector, automotive sector, financial sector and healthcare sector. It also tries to explore the potential applicability of CARMEN in the respective sectors. An analysis of the potential routes to market for CARMEN, along with the proposed pricing methodologies has also been covered in the report. An environmental scanning of the Information Assurance sector of UK along with the present and potential competitors along with their product offerings has also been presented in the report. Based upon the analysis, findings and discussion, the project report proposes recommendations to Nexor for taking CARMEN to the market adequately.